Greening China’s Rural Energy : New Insights on the Potential of Smallholder Biogas - Christiaensen, Luc; Heltberg, Rasmus (World Bank, Washington, DC, 2012)
Clean, safe energy for rural areas is an important component of green growth and sustainable development. Biogas could be an important contributor, if its record in reality lives up to its expected potential. This paper provides a preliminary assessment of biogas use by smallholder farmers in rural China, using data collected from 2,700 households in five provinces. The authors find that user satisfaction is high, and environmental and economic benefits appear tangible. There are strong indications of reduced use of wood and crop residues for fuel. Less time is spent on collecting fuel wood and cooking, which is especially beneficial to women. Adopters also save on fertilizers, because of the use of biogas residues. Moreover, problems with suspension of biogas use, whether due to technical or human factors, remained limited. However, few tangible benefits to respiratory health were detected. Overall, these findings are grounds for optimism about the potential for of smallholder biogas to contribute to more sustainable development, in China and beyond.